The treasures of Alexander the Great : how one man's wealth shaped the world - Holt, Frank L. (Onassis series in Hellenic culture, 2016)
War, the most profitable economic activity in the ancient world, transferred wealth violently through the sacking of cities and the selling of survivors into slavery. One of the most notable examples occurred in the late fourth century BC, when Alexander the Great of Macedonia conquered the Persian Empire. For all of its savagery, this invasion has often been heralded as a positive economic event for all concerned. Even those harshly critical of the king tend to praise his plundering of Persia as a means of liberating the moribund resources of the East. To test that popular interpretation, this book investigates the kinds and quantities of treasure seized by the Macedonian king, from gold and silver to land and slaves. It reveals what became of the king's spoils of war, and what Alexander's redistribution of these vast resources can tell us about his much-disputed policies and priorities